Twenty years of homicide and robbery in Chicago: The impact of the city's changing racial and age composition - Chilton, Roland (Journal of quantitative criminology, 1987)
Uniform Crime Reports (UCR) arrest and offense data for Chicago for 1960 to 1980 and population data from the 1960, 1970, and 1980 censuses are used to assess the extent to which demographic changes help explain trends in the city's homicide and robbery arrests. The results indicate that a changing racial composition contributed to changes in the age composition of Chicago's population as well as to changes in the homicide rate. Age-specific analysis by race and gender suggests that as much as 24% of the total increase in homicide arrests and 45% of the increase in robbery arrests (from 1962 to 1980) can be attributed to an increase in the number of nonwhite men in the population. Increased rates of arrest of nonwhite men appear to account for large parts of the increases in homicide and robbery arrests, with increased rates for white men and nonwhite women also accounting for some of these increases. The paper closes with a discussion of the issues raised by these trends for Chicago and other urban areas.